Miniaturised element frequency selective surface design for high power microwave applications - Kai Wu; Wanye Xu; Peng Li; Jinzhu Zhou; Weiheng Li (IET Microwaves, Antennas & Propagation, 2023)
Abstract A third‐order miniaturised element frequency selective surface (MEFSS) for high‐power microwave (HPM) systems is proposed. The MEFSS design is characterised by the excellent capability to handle high‐power waves and the stable frequency response at large incidence angles. Through combining the particle swarm optimisation algorithm and the equivalent circuit method to improve the efficiency, the design has low resonant temperature while maintaining a low maximum field enhancement factor. A theoretical guide for the selection of substrate parameters in high‐power systems is provided. Instead of being as small as possible, the loss tangent should be properly selected to reach a balance between metal loss and dielectric loss. To the author's best knowledge, it is the first time in‐band low temperature and out‐of‐band high temperature suppression at various incidence angles are realised. The results show that the frequency response remains stable for incident angles up to 60°, and the maximum temperature is reduced from 148°C to 44°C for incident power density of 10 kW/m2. A MEFSS prototype was fabricated, and the transmission coefficients were measured. The full‐wave simulation and measurement results agree well. It has significance to the engineering progress of FSS as radomes for HPM antenna systems.